The versatility of a glycerol-preserved skin allograft as an adjunctive treatment to free flap reconstruction - A. Z. Mat Saad; T. L. Khoo; A. A. Dorai; A. S. Halim (Indian Journal of Plastic Surgery)
Skin allografts have been used in medical practice for over a century owing to their unique composition as a biological dressing. Skin allografts can be obtained in several preparations such as cryopreserved, glycerol-preserved, and fresh allograft. A glycerol-preserved allograft (GPA) was introduced in the early 1980s. It has several advantages compared with other dressings such as ease of processing, storage and transport, lower cost, less antigenicity, antimicrobial properties, and neo-vascularisation promoting properties. Skin allografts are mainly used in the management of severe burn injuries, chronic ulcers, and complex, traumatic wounds. Published reports of the use of skin allografts in association with free flap surgery are few or non existent. We would like to share our experience of several cases of free tissue transfer that utilised GPA as a temporary wound dressing in multiple scenarios. On the basis of this case series, we would like to recommend that a GPA be used as a temporary dressing in conjunction with free flap surgery when required to protect the flap pedicle, allowing time for the edema to subside and the wound can then be closed for a better aesthetic outcome.